Night Hawks a Ruth Galloway mystery - Griffiths, Elly (Boston : Houghton Mifflin Harcourt, 2021)
"There's nothing Ruth Galloway hates more than amateur archaeologists, but when a group of them stumble upon Bronze Age artifacts alongside a dead body, she finds herself thrust into their midst-and into the crosshairs of a string of murders circling ever closer"--
North Norfolk. The Night Hawks, a group of metal detectorists, uncover a Bronze Age hoard on the beach-- near a recently deceased body. Not long after, the same group uncover the apparent murder-suicide of a scientist and his wife at the isolated Black Dog Farm. The farm has long been said to be haunted by the Black Shuck, a spectral hound that appears to people before they die. Ruth Galloway is suspicious of amateur archaeologists, but finds herself thrust into the midst of this group. And the further DCI Nelson probes into the cases, the more intertwined they become. -- adapted from jacket
Sequel to: The lantern men.
Series numeration from goodreads.com.
108979
Keywords: Galloway, Ruth -- (Fictitious character); Women forensic scientists -- Fiction; Archaeology -- Fiction; Archaeologists; Murder -- Investigation; Norfolk (England); Detective and mystery fiction; Mystery fiction